종합병원 MZ세대 신규간호사의 직무몰입과 직무만족의 관계에서 개인-환경적합성의 매개효과 - 박인숙(In Sook Park); 남정자(Jeong Ja Nam); 박미마(Mi Ma Park) (한국간호연구학회지, 2024)
Purpose : This study was to confirm the mediating effect of person-environment fit between job involvement and job satisfaction of new nurses of the MZ generation in general hospitals. Methods : The data collection period for this study was from December 28 to 30, 2023. Data collection was conducted on total 173 MZ generation new nurses who have worked for more than 6 months in a department that provides direct nursing care to patients at a general hospital located in G Province and G Metropolitan City. They are 173 nurses who understand the purpose of this study and agree to participate in the study. Results : There was a significant positive correlation between the participants' job involvement and job satisfaction (r＝.80, p＜.001) and person-environment fit (r＝.43, p＜.001) and job satisfaction was related to person-environment fit (r＝.42, p＜.001). As a result of verifying the mediating effect of person-environment fit in the relationship between job immersion and job satisfaction of MZ generation new nurses, it can be determined that it has a significant effect indirectly. Conclusion : Through this study, it was confirmed that in order to increase the job satisfaction of the MZ generation new nurses, it was necessary to prepare measures to increase job involvement and person-environment fit, which are factors that make them in line with the organization's goals and remain in the organization. KCI Citation Count: 0